Immunity status against tetanus in young migrants: a seroprevalence study - Affanni, Paola; Colucci, Maria Eugenia; Capobianco, Emanuela; Bracchi, Maria Teresa; Zoni, Roberta; Viani, Isabella; Caruso, Luca; Carlone, Lucrezia; Arcuri, Carlo; Veronesi, Licia (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Thanks to the highly effective vaccine, tetanus became sporadic in high-income countries with well-established primary childhood immunization programs, but it is common in low-income countries. The migrants, leaving countries with poor immunization programs or where vaccinations have been interrupted, may represent a new risk group for tetanus in host countries. A seroprevalence study was conducted to estimate the immunological status against tetanus in young migrants without vaccination documentation. Methods: After a careful assessment by vaccination services of the Local Health Authority, all migrants recently arrived in Italy were included in the serosurvey. Titers of anti-tetanus toxoid were measured using a commercial ELISA kit. Subjects were stratified by age and by WHO region. Antibody titers 1.00 IU/ml high protection. Results: From January 2004 to December 2019, 2,326 blood samples were collected. Mean age was 13.9 years with no differences between WHO regions. The percentage of the subjects without protective antibodies was 22.3%, with an intermediate level was 45.2%, with high titer was 32.5%. Among migrant coming from African and Eastern Mediterranean WHO regions, the highest percentages of seronegative titers and, at the same time, the low percentages of high protective levels were found. Titers decreased with age. Conclusions: The significant proportion of seronegative migrants and the decrease of protective titers increasing age, confirm the importance of the evaluation of the immunological status to employ the appropriate vaccination strategy.